Eficácia de um programa de comunicação alternativa aplicado a grupos de escolares com deficiência intelectual - Lima, Cândice da Silva e (2008)
The capability to use the language is essential for the acquisition of the symbolic systems and to improve the interpersonal relationships; his/her full development depends on the cognitive abilities and social adaptative skills. When an implication happens in this natural course, it is common to appear alterations in the communicative process. The speech pathologist s intervention in group, when using Augmentative and Alternative Communication as an intervention procedure, makes possible the complete use of the social interactions in the development of the language abilities. The objective of the present study was to plan, to apply and to evaluate an intervention program about Augmentative and Alternative Communication in a group inserted on a naturalistic model in one Special Education School. The ten students who participated in the research had a diagnosis of intellectual disabilities. Three of them were the target subjects. In order to be the target, they had to be non verbal. In the group of seven children there were some who were verbal and others nonverbal ones. All of the ten participants were capable to accomplish voluntary motor actions and they did not participate in other intervention group that used Augmentative and Alternative Communication. The chronological age of the group varied between 6 and 14 years old. To verify the effects of the intervention Program on Augmentative and Alternative Communication in the participants communicative behavior, a Multiple Baseline design across subjects was used. The sub-test Pragmatic from Test of Infantile Language ABFW and the Test of Receptive and Expressive Language were also used. The Results demonstrated that during the Baseline, none of the participants obtained success in relation to the use of the communication pictures. However, when the intervention process was started, the children presented increase in the use of pictures as an alternative to communicate their needs. At the end of the data collection all children were able to use the picture exchanging program. The Pre and Post results related to the Pragmatics Evaluation revealed that all the participants from each group improved their communicative abilities. It is important to emphasize that some of them improved their verbal behaviors and the ones who did not have conditions to improve their oral communication, started to use the pictures to communicate their needs associated with gestures and vocalizations. The application of Pre and Post Test on Receptive and Expressive Language Test, evidenced changes when the expressive language is analyzed. Some participants acquired abilities related to language verbal expression, even thought this was not the study main focus. We concluded that when the System of Augmentative and Alternative Communication was employed, the development of the communicative abilities occurred, improving the participants' communication performance during the interactions. Therefore, it is evident the importance of the speech pathologist s intervention in group situations and the use of the Communicative Alternative and Augmentative Systems to develop communication skills in children with intellectual disabilities.